PENGARUH PROMOSI TERHADAP KEPUASAN KONSUMEN BERDAMPAK LOYALITAS DALAM BERBELANJA ONLINE PADA SHOPEE - Iis Kartini; Edi Wahyu Wibowo; Eko Sugiyanto (POLITEKNIK LP3I JAKARTA, 2021)
High competition in the retail industry has urged producers to distribute all of their products so that they are accessible to all consumers. Convenience and speed are important factors so that customers can immediately enjoy the most convenient goods to reach quickly. The purpose of this study was to determine how the effect of promotion on customer satisfaction has an impact on loyalty in online shopping at Shopee. This type of research is quantitative with a path analysis system with data collection tools using purposive sampling. The sample in this study were 100 responden who had done online shopping at Shopee. In this study, to test the validity & reliability there are several indicators that are invalid after 3 times of testing, only valid & reliable results can be obtained. From the t-test analysis, it is found that the promotion variable has a positive effect on the satisfaction and customer loyalty variables. Likewise, the consumer satisfaction variable has a positive effect on the loyalty variable in online shopping at Shopee. Even though the results are good, it is suggested that Shopee should increase its offline promotional activities such as making sponsorships, making bazaars or direct sales so that consumers will be more satisfied. This will make consumers more loyal by later being able to provide recommendations to friends / relatives and when there is competition between market places, consumers will still choose Shopee as the first choice of online shopping place.Keywords: Promotion, customer satisfaction, loyalty, online shopping.